HEALTH AND TRAJECTORIES OF LIVING ARRANGEMENTS AMONG YOUNG-OLD AND OLD-OLD AMERICANS. (11th November 2018) - Liang, J; Kim, B; Xu, X; Raymo, J; Ofstedal, M; Zheng, Q; Kim, B
Abstract: Identified by the United Nations as the most pressing issue of population aging, living arrangements are critical to intra-family exchanges that affect older persons' health and well-being. The conventional conceptualization of living arrangements has emphasized intergenerational coresidence with children, while overlooking proximate residence from children. Additionally, existing research is largely based on cross-sectional data, confounding intrapersonal differences with interpersonal variations. Finally, there is limited understanding of the linkages between health and living arrangements. To fill these gaps, this research analyzes the trajectories of living arrangements in old age as a function of health status within the context of social stratification. As part of the Health and Retirement Study, data came from a national sample of 7, 822 older Americans with at least one living child from 1998 to 2014. Multi-level mixed effects models were employed to evaluate the trajectories of living arrangements and their key determinants. Among the young-old (age 65–74, N=4, 917), the probability of coresidence increased slightly over a 16-year period, whereas the probabilities of proximate residence and distant residence decreased slightly and remained stable respectively. Meanwhile, the risk for institutionalization increased moderately. Although a similar pattern of trajectories was observed among the old-old (age 75+, N=2, 905), the rates of changes were much more accelerated. Health status at the baseline and health changes over time were significantly associated with the levels as well as the slopes of the trajectories of living arrangements. These findings would inform public policies to strengthen family-based support and long-term care for older people.